PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN DESAIN DAN PRESTASI BELAJAR (Studi pada mata Pelajaran Produk Kreatif dan Kewirausahaan di kelas XI TKJ - Berthy Anggraini (DIADIK, 2020)
This study aims to describe the application of the Project Based Learning (PJBL) model to improve design skills, learning achievement and the application of the PJBL model in increasing learning achievement of creative and entrepreneurial products. The research was conducted was Classroom Action Research (CAR), which was carried out for 3 cycles. The subjects of this study were students of class XI computer engineering and network of State Vocational High School 2 Lahat in the academic year 2019/2020 with a total of 29 students. with the model, observation sheet of student learning design skills in creative and entrepreneurial product material, and objective tests Data analysis is done by using t-test or difference test to compare learning achievements of each cycle or between cycles. The conclusion of this study is the application of the Model Project Based Learning as well as improving design skills and learning achievement and applying Project Based learning models more effectively to improve student learning achievement, in subjects Creative and entrepreneurial product.